SKULL-BASE MENINGOENCEPHALOCELE PRESENTING AS A LABIOGNATOPALATOSCHIZIS AND BILATERAL MACROSTOMIA ON IMPENDING PARTIAL AIRWAY OBSTRUCTION IN A NEONATE - Nyoman Golden (Indoscholar, 2018)
A unique skull-base meningoencephalocele presenting as a labiognatopalatoschizis and bilateral macrostomia in a neonate is reported, with impending partial airway obstruction. Surgical management requires neurosurgical intervention and plastic reconstruction. This case report presented a term neonate was noted to have a soft, fxed, 5-cm mass fulled of his mouth with the impending partial airway obstruction. The patient had several episodes of apnea related to partial airway obstruction by the mass. Computed tomography (CT) scan showed a large complex cystic and solid mass on lamina cribrosa of ethmoidal bone. Focal calcifcation was seen within the mass. The mass extended resulting in the complete cleft of lip and palate, and bilaterally macrostomia. The brain on CT scan was normal with no dysmorphic structures. A transcranial approach by the neurosurgeon was performed to excise the cephalocele and close the dura mater. The bone defect on lamina cribrosa of ethmoidal bone was closed using periosteum tissue. The procedure was followed by total excision of the prolapsed brain tissue and osteotomy on the left palate and then nasal airway reconstruction continued with gradual reconstruction with external compression for close loopholes of the palate. Three months after the initial surgery, a defect of the palate was narrowing and without cranial nerve defcits. Skull-base transethmoidal meningoencephalocele with labiognatopalatoschizis and bilateral macrostomia is a rare congenital abnormality. Neurosurgical procedures through transcranial approach are safe and provide excellent results. Moreover, gradual reconstruction will improve a patient’s quality of life and activity of daily living